Terminal deoxynucleotidyl transferase activities and glucocorticoid receptors in leukaemia. - Sasaki, R. (Nature Publishing Group, 1981)
The relation between terminal deoxynucleotidyl transferase (TdT) activity, glucocorticoid (GC) receptors and the effect of vincristine-prednisolone (VP) therapy on fresh leukaemia cases was examined. Five of 6 TdT+ leukaemias showed high levels of GC receptors and a favourable response to VP therapy, whereas 1 acute lymphoblastic leukaemia (ALL) and 3 of chronic myelogenous leukaemia (CML) cases in blast crisis with no TdT activity showed low level of GC receptors and poor response to VP therapy. Significant correlation (r = 0.821, P less than 0.01) was observed between TdT activity and the number of GC receptor sites in these cases. X2 test showed significant difference (P less than 0.01) between TdT+ and TdT- leukaemias in the effect of VP. A significant difference (P less than 0.01) was also observed between VP-effective and ineffective leukaemias in the number of GC-receptor sites by unpaired t test. Therefore GC receptors may be responsible for the effect of VP on TdT+ leukaemias.